CONSUMER SHOPPING BEHAVIOR IN INDONESIA AND THAILAND: HEDONIC AND UTILITARIAN SHOPPING VALUES - Pujianto, Hendri; Marwati, Fithri Setya (Jurnal Ekonomi dan Bisnis Airlangga, 2024)
Introduction: Shopping value, which influences shopping experiences, has garnered attention and constitutes a well-studied topic in marketing. This study aimed to measure and describe differences in consumer shopping behavior between Thailand and Indonesia regarding hedonic and utilitarian values. Methods: This study employed a quantitative, descriptive, cross-sectional survey conducted among consumers residing in Indonesia and Thailand. The respondents comprised 70 individuals aged 18 years from Surakarta City and an equivalent number from Nonthaburi City. The data distribution and collection using questionnaires were carried out for 2 months, from July to August 2023. The data analysis was performed by utilizing SPSS software. Notably, both cities are in the process of rapid development into metropolises. Most respondents were women under 25 years old. Results: This study discovered that Indonesian and Thai consumers performed hedonic shopping behaviors. However, consumers with hedonic shopping behaviors in Thailand were more inclined towards impulsive shopping behaviors and engaged in shopping activities out of desire rather than necessity, compared to consumers in Indonesia. Conclusion and suggestion: This study described that both Indonesian and Thai consumers had utilitarian shopping behaviors, enabling them to accomplish their objectives and procure desired items effectively during shopping endeavors. Nonetheless, consumers in Thailand display a tendency to find their desired items and prefer to shop briefly compared to their counterparts in Indonesia. Future researchers would benefit from examining the relationship between consumer behavior and other factors such as age or gender. Understanding the influence of these variables on shopping behavior is crucial for gaining comprehensive insights into consumer preferences and decision-making processes in the retail environment.